Approaching the Bioeconomy in Terms of Increasing the Energy Efficiency of Households in Romania - Gabriel Brătucu; Cristinel Petrișor Constantin; Ioana Bianca Chițu; Evelina Grădinaru; Lavinia Dovleac (Amfiteatru Economic)
This paper approaches the transition process to the bioeconomy from consumers’ perspective and their attitudes to decision-making process regarding the use of renewable energy systems in households. The article contributes to the literature by introducing a new challenge: identifying and analyzing the Romanians’ opinion on increasing the energy efficiency in their households and their intention in using energy obtained from renewable resources. For the purpose, a quantitative marketing research was conducted by interviewing 1123 persons from Romania’s eight development regions. Data were collected using an electronic questionnaire. The research results underline that Romanians have invested in increasing the energy efficiency of their household, the main improvements being energy saving by purchasing low-power home appliances or thermal insulation of the dwelling. These investments were made based on economic considerations, being considered as a long-term benefit for the entire household. The authors propose to the Romanian economic environment to carry out information and promotional campaigns in order to raise awareness of Romanians on the importance of using energy obtained from renewable resources for sustainable development. To the academic environment, the authors recommend including bioeconomics in the curriculum of study programs offered to the education services market